MicroRNA-122 Mimic Improves Stroke Outcomes and Indirectly Inhibits NOS2 After Middle Cerebral Artery Occlusion in Rats - Lv, Bo; Cheng, Xiyuan; Sharp, Frank R.; Ander, Bradley P.; Liu, Da Zhi (Frontiers in Neuroscience, 2018)
Aim: Our previous study demonstrated miR-122 mimic decreased NOS2 expression in blood leucocytes and improved stroke outcomes when given immediately after middle cerebral artery occlusion (MCAO) in rats. Since NOS2 is associated with neuro-inflammation in stroke and decreasing NOS2 expression alone in leucocytes is insufficient to improve stroke outcomes, we hypothesized that miR-122 mimic may also decrease NOS2 expression in brain microvascular endothelial cells (BMVECs) even at extended time windows. Methods: We administered PEG-liposome wrapped miR-122 mimic (2.4 mg/kg, i.v.) 0 or 6 h after MCAO, and assessed stroke volume and NOS2 expression in BMVECs 24 h following MCAO in rats. Luciferase reporter assays were used to determine if miR-122 binds to 3′ untranslated regions (3′UTR) of NOS2. Results: The data showed that miR-122 mimic decreased infarct volumes and decreased MCAO-induced NOS2 over-expression in BMVECs. However, miR-122 did not bind to 3′UTR of NOS2 in the luciferase assays. Conclusion: The data show the 6-h period of therapeutic efficacy of miR-122 mimic which could relate to indirect knockdown of NOS2 in both BMVECs and leucocytes.